Peramalan Jumlah Produksi Kerupuk Kamang Berdasarkan Keuntungan Hasil Produksi Menggunakan Analisis Regresi Invers dengan Metode Klasik - yulistia rahmadani; Helma Helma (UNIVERSITAS NEGERI PADANG, 2021)
The limitation of kamang cracker businessmenin marketing their products is the main factor that makes businessmenunable to maximizethe profits of theirproduction. To maximize profits, a method is needed to predict the number of kamang crackers that must be produced based on the profits obtained. In this case, regression analysis with classical method can be used wherethe value of x0 can be predicted based on the dependent variable y0. The purpose of this study is to create a model and determine the prediction interval from forecasting the numberofkamang cracker production based on the profit obtained from the production. The data used are primary data obtained from 25 business houses inKecamatanKamang Magek . From the prediction results obtained, it can be interpretationthe number of kamangcrackers that must be produced